Is it news - Bramhall, Doyle, II, 1968- (Yep Roc Records, 2007)
Texas blues singer, songwriter, and drummer Doyle Bramhall is joined by fourteen other musicians in performances of twelve songs, including "Lost in the Congo," "Chateau Strut," and "Ooh Wee Baby.".